The impact of ethnic-racial socialization messages from socialization agents on Black ethnic-racial identity - Jones, Denzel Lamont (Kansas State University, 2018)
It is known that ethnic-racial socialization messages received by Black youth are critical to their ethnic-racial identity development. Despite recognition that identity achievement is rarely completed by the end of adolescence and Black youth are embedded in larger multicultural familial, communal, and societal contexts, previous studies almost exclusively focus on parents as the isolated provider of ethnic-racial socialization messages during adolescence. Using a sample of 171 Black emerging adults, this retrospective study focused on the influence of four unique types of ethnic-racial socialization messages from diverse ethnic-racial socialization agents throughout adolescence and emerging adulthood on the development of Black ethnic-racial identity during emerging adulthood. Participants reported that although parents, adult family members, and siblings were the most influential socialization agents during adolescence, they became less influential during emerging adulthood as peers gained more influence. Across all developmental periods, emerging adults reported the strongest messages they received were egalitarian and racial pride messages and the weakest messages they received were negative messages. Additionally, seven different profiles of ethnic-racial identity development during emerging adulthood were identified and were predicted by the types of ethnic-racial socialization messages emerging adults received from adolescence through emerging adulthood. These results highlight the importance of receiving racial pride and racial barrier messages along with minimal egalitarian and negative messages from socialization agents in order to foster a healthy and positive Black ethnic-racial identity during emerging adulthood. Clinical implications, family life education implications, implications for diverse socialization agents, and areas for future research based on the findings of the present study are discussed.
Keywords: Identity development; Black identity; Socialization messages; Socialization agents; Minority identity; Racial identity